Adomas Jakštas textbook "Plokštinė trigonometrija" - Lazauskienė, Aistė (Lietuvos matematikos rinkinys, 1998)
The famous Lithuanian poet and priest Aleksandras Dambrauskas – Adomas Jakštas died sixty years ago. He was highly interested in mathematics. Aleksandras Dambrauskas wrote a few scientific articles on mathematics. Here we present some comments concerning his mathematical textbook "Plokštinė trigonometrija" for gymnasium (published in 1920). It iš one of the very first two textbooks on trigonometry which appeared at that time. We discuss and analyse mathematical terms and topics, presented in this textbook, and emphasize their significance for nowadays pedagogical science.